Molnupiravir and Nirmatrelvir/Ritonavir: Tolerability, Safety, and Adherence in a Retrospective Cohort Study - Maria Mazzitelli; Daniele Mengato; Lolita Sasset; Anna Ferrari; Samuele Gardin; Vincenzo Scaglione; Nicola Bonadiman; Lucrezia Calandrino; Silvia Cavinato; Sabrina Trivellato; Francesca Venturini; Anna Maria Cattelan (Viruses, 2023)
Background. Molnupiravir (MOL) and nirmatrelvir/ritonavir (NIR) were recently approved for the early treatment of COVID-19, but real-life data on tolerability, safety, and adverse events (AEs) are still scarce. Methods. We conducted a retrospective cohort study including all patients who were prescribed MOL and NIR at the Infectious Diseases Unit of Padua University Hospital, between January and May 2022. Demographic, clinical, and safety variables were recorded. Results. We included 909 patients, 48.3% males and 95.2% vaccinated against SARS-CoV-2. The median age was 73 (IQR: 62–82) years. MOL and NIR were prescribed in 407 (44.8%) and 502 (55.2%) patients, respectively. Overall, 124/909 (13.6%) patients experienced any AEs following antivirals intake: 98/124 (79%) patients reporting adverse events presented grade 1 AEs, 23/124 (18.5%) grade 2 AEs and 3 (2.5%) grade 3 AEs. Treatment discontinuation was recorded in 4.8% of patients. AEs were significantly higher in women, in patients treated with NIR compared to MOL and in people who were not vaccinated. Conclusions. In our real-life setting, AEs were higher than those reported by clinical trials, and were particularly associated with NIR use and with not being vaccinated. Further analyses are needed to better assess safety of oral antivirals and to define which patient’s profile may benefit most from MOL and NIR.